If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying g(6) = -2x + 4 Reorder the terms for easier multiplication: 6g = -2x + 4 Reorder the terms: 6g = 4 + -2x Solving 6g = 4 + -2x Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Divide each side by '6'. g = 0.6666666667 + -0.3333333333x Simplifying g = 0.6666666667 + -0.3333333333x
| 15x^2-12x-99=0 | | 11v+8=9v-18 | | 3a+4b=7b-a | | 17x+48=90 | | 4x^2+32x-64=0 | | 6=-7/2y | | 7a-4=4a+5 | | 4x^2+32-64=0 | | y/4=32 | | 23+30+x=90 | | 2(q-3)+6= | | 3-4(x+4)=6x-13 | | f(-2)=-8x-5 | | -6(n+3)+19=-2n-11 | | L=1/2pV^2SC | | 3.2+(h+5.1)= | | Y=(-1/5)-20-2 | | 45/B=15 | | -4-4s=-8-2s | | 63/60=x/180 | | 4a/3=160 | | y/6-3 | | 4x(4x-5b)+3= | | 3+3d= | | 9b^2-48b+48+15b^2-20b=20b-5b^2 | | 22v-9v-8v-v-3v-1=34 | | 100[0.03(p+9)]= | | -28=(4/5)d | | 3x-1+2x^2(6)= | | 7x-(3x-9)= | | 3y+17=-2y+24 | | -6d-10=-5d |